CDKN2A Copy Number Loss Is an Independent Prognostic Factor in HPV-Negative Head and Neck Squamous Cell Carcinoma - Chen, William S.; Bindra, Ranjit S.; Mo, Allen; Hayman, Thomas; Husain, Zain; Contessa, Joseph N.; Gaffney, Stephen G.; Townsend, Jeffrey P.; Yu, James B. (Frontiers in Oncology, 2018)
Background: HPV infection is associated with high p16 expression and good prognosis in head and neck squamous cell carcinomas (HNSCCs). Analysis of CDKN2A, the gene encoding p16, may further elucidate the association between p16 expression and prognosis. We sought to determine whether CDKN2A copy number loss was associated with poor survival in HPV-negative HNSCCs. Methods: The Cancer Genome Atlas (TCGA) HNSCC clinical and genomic data were obtained and integrated. Patients <80 years old with a primary tumor in the oral cavity, oropharynx, hypopharynx, or larynx were included. Stratifying by copy number loss status, CDKN2A mRNA and p16 protein expression levels were examined and overall survival (OS) and disease-free survival (DFS) were evaluated. Results: 401 patients with HPV-negative HNSCC were identified. 146 patients demonstrated CDKN2A copy number loss. The CDKN2A copy number loss group expressed significantly lower levels of CDKN2A mRNA and p16 protein than did the non-copy number loss group. Median OS for patients with and without CDKN2A copy number loss was 16.5 months and 46.6 months respectively (p=0.007). Median DFS for both groups was 11.6 and 19.2 months respectively (p=0.03). In both univariate and multivariable analyses, stage IV designation, receipt of chemotherapy, and CDKN2A copy number loss were predictive of overall survival. Conclusions: CDKN2A copy number loss predicted poor survival independently of other patient and treatment factors and may be a clinically useful prognostic factor.